Islamists and Women in the Arab World - Najib Ghadbian (International Institute of Islamic Thought, 1995)
Introduction Broadly speaking, contemporary discourse assumes that Islamists are bad for women. Any gain in Islamist political influence is considered a disastrous regression in women’s human rights. At a time when the movement to put women’s rights on the international human rights agenda-a valuable movement indeed-seems on the brink of joining the group of world and regional powers targeting Islamists as the next great threat to humanity, it is urgent that Islamists formulate a strong and just analysis of the gender issue. While the stereotypical view of Islamists, like most stereotypes, has some basis, it is, as are all stereotypes, completely inadequate for understanding the issue. The fact that one can locate a Saudi shaykh, an Egyptian imam, or a young Algerian militiaman who is unmistakably misogynistic does not provide the key to understanding the entire range of Islamist views on gender roles or the implications for women of rising Islamist influence. The indictment of Islamists as oppressive to women emerges from the context of western hegemonic power in the world and deploys the language of women’s liberation to justify political and economic assaults against contemporary Islamist states and political forces. The problem is that women do face oppressive conditions in the Muslim world, as do their counterparts in the West, but these are different from the oppressive conditions imagined and constructed for Muslim women from a western frame of reference ...